The beloved world of Sonia Sotomayor - Sotomayor, Sonia, 1954- (Delacorte Press, 2018)
"In this adaptation for middle graders based on her bestselling adult memoir, My Beloved World, Associate Justice of the Supreme Court Sonia Sotomayor's extraordinary life inspires. Her achievement serves as a true testament to the fact that no matter the obstacles, dreams can come true. Includes an 8-page photo insert. Sonia Sotomayor, the first Hispanic and third woman appointed to the Supreme Court of the United States, was a young girl when she dared to dream big. Her dream? To become a lawyer and a judge. As Justice Sotomayor explains, "When I was a child my family was poor and we knew no lawyers or judges and none lived in our neighborhood. I knew nothing about the Supreme Court and how much its work in reinterpreting the Constitution and the laws of the United States affected peoples' lives. You cannot dream of becoming something you don't even know about. That has been the most important lesson of my life. You have to learn to dream big dreams." Sonia did not let the hardships of her background--which included growing up in the rough housing projects of New York City's South Bronx, dealing with juvenile diabetes, coping with parents who argued and fought personal demons, and worrying about money--stand in her way. Always, she believed in herself. Her determination, along with guidance from generous mentors and the unwavering love of her extended Puerto Rican family, propelled her ever forward"--